2020
DOI: 10.23917/jramathedu.v6i1.11630
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive flexibility: exploring students’ problem-solving in elementary school mathematics learning

Abstract: In classroom learning, students need mathematical cognitive flexibility to be able to solve mathematical problems with the various ideas they express. To solve the problems, they must be able to grasp the problem, see it from various points of view, and should not be rigid thinking with one solving method.  In fact, the students still lack the ability to think flexibly in solving math problems. This exploration is necessary to determine how to encourage the students’ creative problem-solving. The purposive sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
0
13
0
7
Order By: Relevance
“…According to research by Purpura et al (2017), working memory played a role in mathematical abilities such as counting, comparisons, and formulating mathematical problems. In contrast, the cognitive flexibility aspect was related to the conceptual element of mathematical ability (Purpura et al, 2017;Rahayuningsih et al, 2020). The findings in students' mathematical literacy skills showed that the PISA indicators could not appear in achieving mathematical literacy skills when solving PISA questions.…”
Section: Discussionmentioning
confidence: 86%
“…According to research by Purpura et al (2017), working memory played a role in mathematical abilities such as counting, comparisons, and formulating mathematical problems. In contrast, the cognitive flexibility aspect was related to the conceptual element of mathematical ability (Purpura et al, 2017;Rahayuningsih et al, 2020). The findings in students' mathematical literacy skills showed that the PISA indicators could not appear in achieving mathematical literacy skills when solving PISA questions.…”
Section: Discussionmentioning
confidence: 86%
“…Matematika merupakan perantara berpikir ilmiah dalam mengembangkan kemampuan dan keterampilan intelektial siswa, dengan demikian siswa mampu menyelesaikan masalah yang berkaitan dengan matematika maupun ilmu lain (Holis et al, 2016). Menurut (Rahayuningsih et al, 2020), pemecahan masalah adalah salah satu aspek utama dari kurikulum matematika yang tidak hanya berlaku di Indonesia tetapi juga di seluruh dunia. Sehingga saat ini siswa di tuntut untuk dapat berpikir secara logis dan kritis dalam menyelesaikan berbagai permasalahan matemaika.…”
Section: Pendahuluanunclassified
“…The Mathematics Creative Thinking Ability Scale was developed based on the research instrument of Rahayuningsih et al (2020). It contains an indicator of creative thinking ability that is cognitive flexibility (Singer et al, 2017& Rahayuningsih et al 2020).…”
Section: Mathematics Creative Thinking Ability Scalementioning
confidence: 99%
“…The Mathematics Creative Thinking Ability Scale was developed based on the research instrument of Rahayuningsih et al (2020). It contains an indicator of creative thinking ability that is cognitive flexibility (Singer et al, 2017& Rahayuningsih et al 2020). According to Singer et al, (2017), the context used to examine students' creativity in mathematics involves mathematics tasks, like problem-solving sheets, that can be used as an instrument to measure students' mathematical creative thinking ability.…”
Section: Mathematics Creative Thinking Ability Scalementioning
confidence: 99%